The effect of fetal calf serum concentrations upon the in vitro Bos taurus indicus X Bos taurus taurus crossbred embryo production and the cytoplasmic lipid accumulation - Sudano, Mateus José [UNESP]; Paschoal, Daniela Martins [UNESP]; Rascado, Tatiana da Silva [UNESP]; Lima Neto, João Ferreira [UNESP]; Alvarenga, Fernanda da Cruz Landim e [UNESP] (My University, 2011)
The aim was to test the supplementation of five different concentrations of fetal calf serum (FCS) upon the in vitro production (IVP) and cytoplasmic lipid accumulation in Nelore and Simmental crossbred bovine embryos. The addition of serum started on D3 of embryo culture. Nelore oocytes were submitted to in vitro maturation, in vitro fertilization with Simmental semen, and in vitro cultured. From D1 to D3 it was used the SOFaa media + 0.5% BSA without serum (Base Media). From D4 to D7 the embryos were divided into four experimental groups according to the concentration of serum that was added to the Base media: Group 0-0%: without serum; Group 0 – 2.5%: 2.5% of serum; Group 0-5%: 5% of serum; and Group 0-10%: 10% of serum. As for the Control group it was used Base Media + 2.5% of serum from D1 to D7. Statistical analysis was done with ANOVA followed by the Tukey test (P0.05) when assessing cleavage (72.74±3.18%, 84.18±0.74%, 68.46±2.35%, 75.72±1.77%, 81.07±3.38%), blastocyst formation (32.62±0.59%, 27.27±0.93%, 27.04±2.25%, 30.31±1.31%, 37.13±1.50%), development stage (5.16±1.12, 5.01±1.10, 5.06±1.02, 4.98±0.99, 5.21±1.04) and embryo quality (2.80±1.39, 2.89±1.36, 2.99±1.33, 2.78±1.42, 2.65±1.39), for the groups Control, 0-0%, 0-2.5%, 0-5% e 0-10%, respectively. However, the increase of serum concentration in the embryo culture media showed an increase of medium and large, lipid droplets. Nevertheless, for the groups with lower concentrations of serum (0-0% e 0-2.5%) the number of small lipid droplets was similar to the ones with higher concentrations (0-5% e 0-10%). We can conclude that it is possible to perform the IVP with no supplementation of serum in culture media, without producing any negative effect upon the production, development, and embryo quality.

El objetivo fue estudiar la suplementación de cinco diferentes concentraciones de suero fetal bovino (SFB) en la producción in vitro (PIV) y la acumulación de lípidos citoplasmáticos en embriones bovinos obtenidos desde el cruce de Nellore con el Simmental. Ovário de matadero de vacas fueron utilizados para obtener los ovocitos y fueron madurados in vitro. Después de la fecundación in vitro con semen de un toro Simmental, los cigotos posibles se talaron y se transferirán a las placas de cultivo. De D1 a D3 fue utilizado el SOFaa + 5% de BSA con 0% de SFB. De D4 a D7 los embriones fueron divididos en cuatro grupos de acuerdo con la concentración de SFB en el medio de cultura: Grupo 0-0%: SOFaa + 5% de BSA (medio base); Grupo de 0-2,5%: medio base + 2,5% de SFB, 0-5% Grupo: medio base + 5% de SFB y Grupo 0-10%: medio base + 10% de SFB. Como control se utilizó un sistema de cultivo que contiene 2,5% de suero fetal bovino de D1 a D7. Para análisis estadística fue usado ANOVA seguido del Test de Tukey (P 0,05) y la escisión (72,74 ± 3,18%, 84,18 ± 0,74%, 68,46 ± 2,35%, 75,72 ± 1,77%, 81,07 ± 3,38%), la formación de blastocistos (32,62 ± 0,59%, 27,27 ± 0,93%, 27,04 ± 2,25%, 30,31 ± 1,31%, 37,13 ± 1,50%), la etapa de desarrollo (5,16 ± 1,12, 5,01 ± 1,10, 5,06 ± 1,02, 4,98 ± 0,99, 5,21 ± 1,04) y el grado de calidad de embriones (2,80 ± 1,39, 2,89 ± 1,36, 2,99 ± 1,33, 2,78 ± 1,42, 2,65 ± 1,39), respectivamente para el grupo de control, 0-0%, 0-2.5%, 0-5% y 0-10%. Sin embargo, al aumentar la concentración de SFB en el centro de desarrollo del embrión, se observó un aumento en la acumulación de gotitas de lípidos medianas y grandes. Sin embargo, en aquellos con menores concentraciones de suero (0-0% y 0-2,5%) el número de pequeñas gotitas de lípidos fue similar a los grupos con mayores concentraciones (0-5% y 0-10%). Se concluye que la PIV es posible sin la suplementación del medio de cultivo con suero fetal bovino, sin afectar la producción, el desarrollo y la calidad del embrión.

O objetivo deste trabalho foi estudar a suplementação de cinco diferentes concentrações de soro fetal bovino (SFB), a partir do terceiro dia do cultivo embrionário, sobre a produção in vitro (PIV) e o acúmulo lipídico citoplasmático de embriões bovinos oriundos do cruzamento da raça Nelore com a raça Simental. Ovários de abatedouro de vacas Nelore foram utilizados para a obtenção dos oócitos que foram maturados in vitro. Decorrida a fertilização in vitro com o sêmen de um touro Simental, os possíveis zigotos foram desnudos e transferidos para as placas de cultivo. Do D1 ao D3 utilizou-se o meio SOFaa + 5% BSA com 0% de SFB. Do D4 ao D7 os embriões foram distribuídos em quatro grupos experimentais de acordo com a concentração de SFB adicionada ao meio de cultivo: Grupo 0-0%: SOFaa + 5% BSA (meio base), Grupo 0 – 2,5%: Meio base + 2,5% de SFB, Grupo 0-5%: Meio base + 5% de SFB e Grupo 0-10%: Meio Base acrescido de 10% de SFB. Como grupo controle foi utilizado um sistema de cultivo contendo 2,5% de SFB do D1 ao D7. Para análise estatística utilizou-se ANOVA seguido do Teste de Tukey (P0,05) quanto a clivagem (72,74±3,18%, 84,18±0,74%, 68,46±2,35%, 75,72±1,77%, 81,07±3,38%), a formação de blastocistos (32,62±0,59%, 27,27±0,93%, 27,04±2,25%, 30,31±1,31%, 37,13±1,50%), o estágio de desenvolvimento (5,16±1,12, 5,01±1,10, 5,06±1,02, 4,98±0,99, 5,21±1,04) e grau de qualidade embrionária (2,80±1,39, 2,89±1,36, 2,99±1,33, 2,78±1,42, 2,65±1,39), respectivamente para os grupos controle, 0-0%, 0-2,5%, 0-5% e 0-10%. Apesar disso, com o aumento da concentração do SFB no meio de cultivo embrionário, foi observada uma elevação no acúmulo de gotas lipídicas médias e grandes. No entanto, nos grupos com menores concentrações de soro (0-0% e 0-2.5%) o número de gotas lipídicas pequenas foi similar ao dos grupos com maiores concentrações (0-5% e 0-10%). Conclui-se que é possível a PIV sem a suplementação do meio de cultivo com SFB, não afetando a produção, o desenvolvimento e a qualidade embrionária.
Efecto de la concentración del suero fetal bovino en la producción in vitro y la acumulación de lípidos citoplasmáticos en los embriones cruzados Bos taurus indicus x Bos taurus taurus
Efeito da concentração do soro fetal bovino sobre a produção in vitro e acúmulo lipídico citoplasmático em embriões cruzados Bos taurus indicus x Bos taurus taurus
Keywords: In vitro embryo production; Fetal calf serum; Lipid accumulation; Bos taurus indicus; Bos taurus taurus; Producción in vitro; Suero fetal bovino; Acumulación de lípidos; Bos taurus indicus; Bos taurus; Produção in vitro; Soro fetal bovino; Acúmulo lipídico; Bos taurus indicus; Bos taurus taurus